The Impact of Direct Strategies on ESP University Students’ Achievement in Reading Comprehension (Journal of the College of Education for Women, 2025)
Reading is one of foreign language receptive skills, that plays a great role in people lives. It is not a simple skill, it is related to understanding and comprehending the text. Many studies assert that EFL learners face difficulties in reading comprehension skill, so that teachers have to use the appropriate teaching strategies to improve this skill. Direct strategies are those strategies that require students to recover information and develop their reading skill because such strategies require the use of variety of tasks and strategies (memory, cognitive and compensation strategies). The present study aims at finding out the impact of direct strategies on M.A ESP university students achievement in reading comprehension. The following null hypothesis will be examined: there is no statistically significant difference between the achievement of students who are taught reading comprehension by direct strategies and those who are not. Two groups were chosen from M.A ESP students- History Department/ college of education for women/ university of Baghdad, during the academic year (2023-2024). One was chosen as the experimental group (Hadeeth Group), the other one was chosen to be the control group (Islamic Group). Both groups were pre and post tested. T-test for two independent samples is used, it is found that there is a statistically significant difference in the experimental group achievement than the control group because of direct strategies influence. At the end, conclusions based on the results of the study are presented.